2014
DOI: 10.5588/ijtld.13.0021
|View full text |Cite
|
Sign up to set email alerts
|

A molecular transport medium for collection, inactivation, transport, and detection of <I>Mycobacterium tuberculosis</I>

Abstract: In many parts of the world, the diagnosis of tuberculosis (TB) has rapidly shifted to molecular detection and sequencing formats. The collection and transport of Mycobacterium tuberculosis specimens thus remains a challenging problem where TB is common and the infrastructure required for ensuring sample integrity is lacking. PrimeStore(®) Molecular Transport Medium (MTM) addresses this problem, rapidly inactivating/killing M. tuberculosis while preserving genomic DNA even at elevated temperatures for subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…The rapid inactivation is in line with findings from Daum et al (2014), which showed that PS-MTM is an effective medium to inactivate a pure culture of M. tuberculosis at ~10 6 CFU/ml at an exposure time of 30 minutes. This is a similar effect as achieved by the Xpert SR buffer where an 8 and 9 log reduction was demonstrated at 15 minutes and 2 hours respectively (Helb, et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The rapid inactivation is in line with findings from Daum et al (2014), which showed that PS-MTM is an effective medium to inactivate a pure culture of M. tuberculosis at ~10 6 CFU/ml at an exposure time of 30 minutes. This is a similar effect as achieved by the Xpert SR buffer where an 8 and 9 log reduction was demonstrated at 15 minutes and 2 hours respectively (Helb, et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…Expanding potential use of PS-MTM to TB diagnostics, a recent study of PS-MTM showed inactivation within 30 min of M. tuberculosis at a bacillary load of 10 6 CFU/ml (Daum et al, 2014). Based on the relatively scant information on the use of PS-MTM for TB diagnosis and research, as indicated above, insight into its potential application in routine diagnostics of TB is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that this is a safe way of transporting sputum specimens as PS‐MTM inactivates the bacilli, thereby making it safe from an infection control perspective, and that stability of DNA is achieved over time at ambient temperature . These findings concurred with previous studies evaluating these technical properties . In our laboratory evaluation, we further demonstrated good sensitivity and specificity of IS6110 real‐time PCR detection of M. tuberculosis from clinical samples inoculated into PS‐MTM .…”
Section: Discussionsupporting
confidence: 88%
“…The sputum samples were placed on ice immediately after collection and within an hour of collection.~0.5 ml of sputum was transferred to Primestore Molecular Transport Media (Longhorn Vaccines and Diagnostics) vial already containing 1.5 ml of a proprietary mixture of components meant to kill and lyse M . tb in the sputum and to retain the integrity of the released nucleic acid [14,15] as per the PrimeStore manufacturer’s instructions. For optimization of RNA isolation techniques from sputum samples in Primestore, M .…”
Section: Methodsmentioning
confidence: 99%